2010
DOI: 10.1177/0306624x09356683
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Overall Recidivism and Severity of Recidivism in Serious Juvenile Offenders

Abstract: This study was aimed at finding risk factors that predict both overall recidivism and severity of recidivism in serious juvenile offenders. Seventy static and dynamic risk factors associated with family characteristics, peers, psychopathology, substance abuse, psychological factors, and behavior during treatment were assessed with the Juvenile Forensic Profile in a sample of 728 juvenile offenders. Official reconviction data were used to register recidivism with a minimum time at risk of 2 years. Severity of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
92
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 28 publications
9
92
1
5
Order By: Relevance
“…The aim of the present study is therefore to analyse risk and protective factors in relation to youth recidivism by examining their possible differential contribution over a follow-up period of two years, when most recidivist acts take place (Mulder, Brand, Bullens & van Marle, 2011). The study includes outcome variables of recidivism as a state (presence/absence), but also its frequency (number of new criminal charges in the Juvenile Court).…”
mentioning
confidence: 99%
“…The aim of the present study is therefore to analyse risk and protective factors in relation to youth recidivism by examining their possible differential contribution over a follow-up period of two years, when most recidivist acts take place (Mulder, Brand, Bullens & van Marle, 2011). The study includes outcome variables of recidivism as a state (presence/absence), but also its frequency (number of new criminal charges in the Juvenile Court).…”
mentioning
confidence: 99%
“…In addition, the variables level of risk of re-offending as Type of intervention on youth re-offending 6 well as the youth's gender have also been included, since their effect on the type of intervention has been highlighted in several studies (Schwalbe et al, 2012;Wilson & Hoge, 2013a;RodrĂ­guez, 2007;Hayes & Daly, 2004). Moreover, the level of risk of re-offending is easily evaluated by means of an objective procedure, and there is a follow-up period of two years, since it has been shown that most re-offending takes place within that time (Bravo, Sierra & del Valle, 2009;Capdevila et al, 2005;Mulder, Brand, Bullens & van Marle, 2011).…”
mentioning
confidence: 99%
“…These risk factors were selected given their robust associations with offending in community, clinical, and forensic samples (e.g., Farrington, 1998;Loeber & Hay, 1997;Mulder, Brand, Bullens, & Van Marle, 2010).…”
Section: Purpose Of the Present Studymentioning
confidence: 99%